Analysis of the 800-m freestyle competition across age groups: recommendations for master swimmers` performance - Demarie, S.; Guidotti, F.; Pizzuti, A.; Capranicia, L. (Medicina dello Sport, 2023)
BACKGROUND: Athletes must manage their energy expenditure properly both during training and competition to maintain health and avoid injuries. Compared to elite swimmers, master swimmers have lower performance, energy, and swimming efficiency. By adjusting their pace control, master athletes can improve their performance efficiency or results. This study aimed to provide endurance master swimmers with guidance on how to implement the distribution of effort for best results. METHODS: In total, 113 results from the 800 m freestyle finals at the long course world championships in 2023 were examined. Race time % record time (Time%), Coefficient of variation in velocity along the race (CV%) and Normalized velocity of each split as percentage of the mean individual split times (NV%) have been analyzed. RESULTS: The results showed that age-groups differ greatly in their pacing strategies. Masters aged up to 84 years followed a strategy close to elite swimmers, while those aged from 85 to 94 years presented many deviations from the pacing strategy of elite swimmers. Furthermore, the coefficient of variation of velocity resulted highly correlated with the competition performance. CONCLUSIONS: Master endurance swimmers may benefit from maintaining constant speed during 800-m freestyle competitions.